The Gender Implications of Public Sector Downsizing : The Reform Program of Vietnam - Rama, Martin (World Bank, Washington, DC, 2014)
Men and women may be affected differently by the transition from central planning to a market economy and especially by the privatization and restructuring of state-owned enterprises. After briefly reviewing the international evidence on this issue, the author looks at the recent experience of Vietnam and the prospects of its new reform program. During the massive downsizing in Vietnam in the early 1990s, many more women than men were laid off. Women withdrew from the labor force in larger numbers than men after separation, but the difference nearly vanished after a year. Economic reforms were associated with a considerable decline in the gender gap in earnings, both in the state sector and outside it. Women are less likely to be retrenched in large numbers in the downsizing in the early part of this decade. Labor redundancies are concentrated in male-dominated sectors, such as mining, transport, and construction; redundancies are smaller in female-dominated sectors, such as footwear, textiles, and garments. Moreover, temporary and short-term contracts are more prevalent in female-dominated sectors, suggesting demand for women's work. Assistance programs for redundant workers have potential gender biases. The authors shows that separation packages defined as a multiple of earnings favor men more, while lump-sum packages favor women more. Packages based on seniority are roughly gender neutral, but require a substantially higher expenditure to reach the same acceptance rate as the other two.